2022
DOI: 10.1111/1440-1703.12325
|View full text |Cite
|
Sign up to set email alerts
|

Understanding rural and urban perceptions of seagrass ecosystem services for their blue carbon conservation strategies in the Philippines

Abstract: Seagrass meadows provide diverse ecosystem services that directly or indirectly benefit the coastal communities. Despite this, they are among the most threatened coastal ecosystems. Though coastal and marine conservation actions have progressed over the years, seagrasses received less attention compared with other more charismatic ecosystems such as coral reefs and mangroves. Among

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 77 publications
(156 reference statements)
0
6
0
Order By: Relevance
“…In greater Southeast Asia, there is the challenge of socio-economic and cultural disconnect for the seagrass ecosystems due to the lack of appreciation and understanding of seagrass utilization and value (Fortes et al 2018 ). Thus, capacity building of coastal communities to increase the awareness and utilization of seagrass ecosystem services, which is beneficial for the socio-economic aspects (e.g., fishing and gleaning livelihood source, tourism potential) (Quevedo et al 2022 ), will be needed as an integral part of the NbS management.…”
Section: Criterion 1: Seagrass Restorations Address Societal Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…In greater Southeast Asia, there is the challenge of socio-economic and cultural disconnect for the seagrass ecosystems due to the lack of appreciation and understanding of seagrass utilization and value (Fortes et al 2018 ). Thus, capacity building of coastal communities to increase the awareness and utilization of seagrass ecosystem services, which is beneficial for the socio-economic aspects (e.g., fishing and gleaning livelihood source, tourism potential) (Quevedo et al 2022 ), will be needed as an integral part of the NbS management.…”
Section: Criterion 1: Seagrass Restorations Address Societal Challengesmentioning
confidence: 99%
“…Seagrass meadows are among the most important and productive marine ecosystems globally, providing multiple and essential ecosystem services that directly or indirectly benefit people (Cullen-Unsworth et al 2014 ). For instance, seagrass meadows provide a habitat for multiple life stages of commercially valuable fishes and invertebrates, support local communities as food and livelihood sources, improve water quality, stabilize sediment and prevent resuspension, and offer coastal protection services by attenuating wave and tidal current energy (e.g., Fourqurean et al 2012 ; Christianen et al 2013 ; Unsworth et al 2014 ; Quevedo et al 2020 , 2022 ; McKenzie et al 2021 ). Additionally, seagrasses along with mangroves and salt marshes, collectively known as blue carbon ecosystems (BCEs), have gained renewed global attention for their essential role in climate change mitigation (Duarte et al 2013 ) because of their efficient sediment accumulation capacity, which makes them sequester and store organic carbon in sediments for the long term (Miyajima et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the spatial extent of seagrass habitats is less than 2% of global ocean areas, studies have shown that these valuable vegetations are 10 times more effective in capturing carbon dioxide on a per‐area basis per year than terrestrial forests (Mcleod et al, 2011), and about twice more effective in storing organic carbon in their sediment (Murray et al, 2011). In addition, seagrass ecosystems provide many other essential services to coastal communities including coastal protection (James et al, 2019), water quality improvements (Barbier et al, 2011), nursery and foraging habitat for commercially important fish and invertebrates (Boström et al, 2014; Jackson et al, 2015), food and livelihood sources (Quevedo et al, 2022), and tourism services (Nordlund et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in Indonesia, to improve seagrass awareness in the country, the establishment of information boards in all seagrass areas is needed, especially in regions near residential areas, linking national agendas to local settings (Rifai, Hernawan, et al, 2022). Understanding community perceptions of seagrasses particularly in local settings is a critical step for integrated conservation efforts (Quevedo et al, 2020b, 2022). In addition, examining the perceptions of different local stakeholders on ecosystem management is a vital aspect to be considered in “bottom‐up” measures for conservation programs through community‐based management (Lukman, Uchiyama, Quevedo, & Kohsaka, 2021; Quevedo et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%